Complex morphometric effects of sex and aging on subcortical brain structures (N = 9, 872): Neuroimaging / imaging and genetics. (7th December 2020) - Ching, Christopher; Abaryan, Zvart; Zhu, Alyssa; Bright, Joanna; Jahanshad, Neda; Thompson, Paul M
Abstract: Background: Much remains to be understood about subcortical brain alterations across the lifespan and how such changes are related to sex and genetic risk for dementia. Here we analyze the effect of sex, age and APOE genotype on subcortical volume and high‐resolution morphometry in a large population‐based sample. We hypothesized that shape analysis would reveal complex age and sex effects not revealed by gross volumetric analysis and that each copy of the APOE 4 alele would be associated with smaller hippocampal volume. Method: T1‐weighted brain MRI data (N=9, 872) from the UK Biobank were processed using FreeSurfer v5.3 to derive bilateral hippocampus, thalamus, putamen, pallidum, amygdala, caudate, nucleus accumbens, lateral ventricle and intracranial volumes (ICV). The ENIGMA Shape Analysis Pipeline was used to compute local thickness and surface area (SA) metrics for up to 2, 502 vertices along each structure's surface (Figure 1). Linear regression was used to model age (44‐79 yrs), sex, age‐by‐sex interactions, and APOE genotype (Table 1) associations with gross volumes and shape metrics while adjusting for age 2, ICV, years of education and body mass index, and adjusting for multiple comparisons. Result: Older individuals had generally lower gross volumes and larger lateral ventricles (Table 2). Males tended to have larger volumes compared to females (Table 2), though shape analysis revealed subregions that were larger in females (Figure 2). In the full cohort, a significant age‐by‐sex interaction showed males had lower volumes with increasing age. However, in individuals over 60, this interaction was significantly attenuated (Table 2). Shape analysis revealed age‐by‐sex interactions to be more complex, with females displaying subregions of lower thickness and SA with increasing age. No effect of APOE genotype nor interaction between age, sex and genotype were observed, possibly due to small samples of APOE e2/2 and e4/4 genotypes. Conclusion: Here we show that age and sex effects on subcortical structures may be more complex when modeled using local shape morphometric features. While males tended to lose volume faster than females over the full age span, these effects were weaker at more advanced ages (>60), indicating potentially complex and differential brain aging patterns in men and women.